A Neurologist's Guide to REM Sleep Behavior Disorder - Roguski, Amber; Rayment, Dane; Whone, Alan L.; Jones, Matt W.; Rolinski, Michal (Frontiers in Neurology, 2020)
REM Sleep Behaviour Disorder (RBD) is a chronic sleep condition characterised by dream enactment and loss of REM atonia. Individuals often present to clinic with complaints of injury to themselves or their bed-partner due to violent movements during sleep. RBD patients have a high risk of developing one of the neurodegenerative α-synucleinopathy diseases: over 70% will develop parkinsonism or dementia within 12 years of their diagnosis. RBD patients also exhibit accelerated disease progression and a more severe phenotype than α-synucleinopathy sufferers without RBD. The disease’s low prevalence and the relatively limited awareness of the condition amongst medical professionals, make the diagnosis and treatment of RBD challenging. Uncertainty in patient management is further exacerbated by a lack of clinical guidelines for RBD patient care. There are no binary prognostic markers for RBD disease course and there are no clinical guidelines for neurodegeneration scaling or tracking in these patients. Both clinicians and patients are therefore forced to deal with uncertain outcomes. In this review, we summarise RBD pathology and differential diagnoses, diagnostic and treatment guidelines as well as prognostic recommendations with a look to current research in the scientific field. We aim to raise awareness and develop a framework for best practice for RBD patient management.